An Analysis of The Communicative Way for Peace of Dalailama,The 14th According to Buddhist Peaceful Mean - Sutthirak, Wilawan (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
This purport aims to 1) study the communicative way of Dalai Lama, the 14th,2) to study communication according to the principle of Subhãsitavãcã: Well-spoken Speech, and 3) to analytically study the communicative way of Dalai Lama, the 14thfor peace according to Buddhist peaceful means. From the research, it is found the followings: 1) The communicative way of Dalai Lama, the 14th,the Tibetans’spiritual leader, comprises of his own identity in full of compassion as the foundation of one same family and of forgiveness as the essence of making this world peaceful; hence, his communication emphasizes the inner peace. 2) The communication with Subhãsitavãcã: Well-spoken Speech is of the speaking at the proper time, true, with sweet words, comprising of usefulness and the mind of loving kindness; it is useful communication having influence towards the receivers to change their knowledge, attitudes and listening behavior in adjusting themselves to understand things with reasons. 3) The 14th Dalai Lama, former president who have to communicate in variety with Tibetan and gobble in which to peace negotiation between Tibet and China. He follows on Buddhist peaceful way to press his wishes to society. He is not only the leader of protester to coordinate peace negotiation, he also has the leader of promoting Mahayana Buddhism by inspiring and engaging the society to resolve problems by using peace way.